2021
DOI: 10.1007/s10856-021-06533-7
|View full text |Cite
|
Sign up to set email alerts
|

The immunogenic reaction and bone defect repair function of ε-poly-L-lysine (EPL)-coated nanoscale PCL/HA scaffold in rabbit calvarial bone defect

Abstract: Tissue engineering is a promising strategy for bone tissue defect reconstruction. Immunogenic reaction, which was induced by scaffolds degradation or contaminating microorganism, influence cellular activity, compromise the efficiency of tissue engineering, or eventually lead to the failure of regeneration. Inhibiting excessive immune response through modulating scaffold is critical important to promote tissue regeneration. Our previous study showed that ε-poly-L-lysine (EPL)-coated nanoscale polycaprolactone/h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 51 publications
0
22
0
1
Order By: Relevance
“…Large-scale defects of maxillofacial bone tissue can be caused by oral and maxillofacial trauma, tumours, and congenital deformities, etc., thus seriously affecting the masticatory function, pronunciation, and appearance of patients ( Tatullo et al, 2015 ). Fortunately, defects of bone can be repaired to a favourable extent with tissue engineering technology ( El-Rashidy et al, 2017 ), and ideal bioscaffold material applied in which should possess good biocompatibility, degradability, suitable degradation rate and biomechanical strength, good cell-interface relationship, and structure that is easy to process ( Cui et al, 2018 ; Tian et al, 2021 ). In this study, it was observed that the porosity, pore size, and mechanical properties of HG-HA-TCP scaffold were similar to those of G-HA-TCP scaffold, which met the needs of bone tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…Large-scale defects of maxillofacial bone tissue can be caused by oral and maxillofacial trauma, tumours, and congenital deformities, etc., thus seriously affecting the masticatory function, pronunciation, and appearance of patients ( Tatullo et al, 2015 ). Fortunately, defects of bone can be repaired to a favourable extent with tissue engineering technology ( El-Rashidy et al, 2017 ), and ideal bioscaffold material applied in which should possess good biocompatibility, degradability, suitable degradation rate and biomechanical strength, good cell-interface relationship, and structure that is easy to process ( Cui et al, 2018 ; Tian et al, 2021 ). In this study, it was observed that the porosity, pore size, and mechanical properties of HG-HA-TCP scaffold were similar to those of G-HA-TCP scaffold, which met the needs of bone tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 120 stations are collected and measured at the construction gap, which takes 3 days. It is necessary to determine the conversion parameters between each coordinate system and combine the point clouds obtained by each station into a unified coordinate system so as to obtain a complete point cloud model of the target, that is, multistation splicing [7][8][9]. According to the compass, tilt compensator, altimeter, and other sensors of the laser scanner, the point cloud can be spliced automatically.…”
Section: Scanning Measurement Scheme Station Location E Building Of S...mentioning
confidence: 99%
“…In the architectural design stage, the BIM model generally carries out a collaborative design based on the information, drawings, or three-dimensional models provided by civil engineering, electromechanical, and other disciplines involved in the building [7][8][9][10]. During construction, the construction process is generally carried out in stages according to a certain sequence, including the earthwork stage, piling stage, masonry stage, structure stage, waterproof stage, and decoration stage [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The initial infiltration of T cells will gradually disappear, and the second wave gathers in the callus about 2 weeks after bone fracture to play a repairing role and support bone regeneration (Könnecke et al, 2014). Different populations of T cells have different impact, and T H 1 and T H 17 are usually regarded as pro-inflammatory subtypes and T H 2 and Treg cells are anti-inflammatory ones (Tian et al, 2021). Although the understanding of the paradigm has been updated and enriched now, it is well acknowledged that the abnormal transformation of T-cell subsets leads to prolonged inflammatory reaction and unsatisfactory repairing outcome, and their balance is particularly important for favorable bone regeneration (Schlundt et al, 2019).…”
Section: Bone Repairmentioning
confidence: 99%